Administrative Power Dispute Analysis at the Rainha Da Paz–Timor Leste Foundation School Case Studies - Pedro Loe Gouveia Leite (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The Timor Leste Rainha da Paz Foundation School has problems with administrative power disputes for 5-10 years, thus affecting the teaching and learning processes at the school. The aim of this research is to find/obtain useful solutions and recommendations and to insure the stability of administrative work and also learning and teaching processes. This research uses qualitative and quantitative through the SWOT analysis system. The result of this research show that the Rainha da Paz-Timor Leste School Foundation is currently being controlled by the founding members who are still actively serving voluntarily from 2002-2024, has carried out the dismissal of founding members who neglected their duties for more then seventeen years. By the way those founders of deserters have not remained silent, but they have also filed a lawsuit and have sold one of the school buildings in the Bebonuk Tribe to the nuns. The founders who are still actively serving voluntarily also believe that this means that the gonogyny property rights or the foundation’s assets have been divided, private foundation founders who got opportunity to become the foundation rulers, they abuse of power and trust, document forgery, and aggravated fraud. The solution to the problem is distribution of foundation assets; Accountability for actions related to criminal law; Prepare the new foundation document and review the institutional constitution statute before retracting or register in Diração Nacional Registo de Notariado (DNRN) the Timor Leste’s Ministry of Justice to obtain the legal rights.